BIOLOGICAL THERAPY IN PEDIATRIC RHEUMATOLOGY (World Bulletin of Public Health, 2024)
The article presents data on unique world experience in the use of biological agents in pediatric rheumatology. Treatment with genetically engineered biological drugs improves the quality of life of children with JA and their families, ensures normal growth and development of young patients, and changes the prognosis of this previously practically incurable chronic autoimmune disease.
Keywords: Children; Biological Therapy; Rheumatology